Microalgae-derived antioxidants and antimicrobials: a sustainable approach for natural food preservatives - Singh, Laishram Amarjit; Kumari, Pritee; Kumar, Priyanshu; Yadav, Ankush; Bhardwaj, Rupesh; Swapnil, Prashant; Meena, Mukesh (Frontiers in Sustainable Food Systems, 2025)
Artificial preservatives such as nitrates, benzoates, sulphites, sorbates, parabens, formaldehyde, butylated hydroxytoluene (BHT), and butylated hydroxyanisole (BHA) have been used for ages to extend the shelf life of food items. However, increasing scientific evidence links their excessive intake to severe health hazards like cancer, endocrine disruption, allergies, and neurotoxicity. As people become more aware and prefer natural clean-label foods, the demand for safer options from the industry is growing. In this situation microalgae can be a strong natural source of preservatives. They are rich in active compounds that show both antioxidant and antimicrobial effects. Microalgal extracts give a green way to improve food safety and shelf life. This review discusses major antioxidant constituents of microalgae, including carotenoids (e.g., astaxanthin, β-carotene), phenolics, and vitamins that reduce oxidative degradation of food matrices. Mechanisms of action, delivery modes, and incorporation into active packaging and food coatings are covered. Despite efficiency challenges associated with extraction, compound stability, and large-scale industrial production, breakthroughs in bioprocessing and biotechnology are rapidly expanding the boundaries of commercial application. In summary, microalgal bioactives offer a promising and sustainable approach to natural food preservation and safety, while also addressing consumer demand for cleaner and safer food products.